Influence of sport type and interdependence on the developmental experiences of youth male athletes - Bruner, M. W.; Hall, J.; Côté, J. (European Journal of Sport Science, 2011)
The purpose of this study was to examine the relationships between sport type, interdependence (task and outcome), and the developmental experiences of select male basketball players (n=129) and middle-distance runners (n=83) aged 14-17 years. Athletes completed the Youth Experiences Survey 2.0 (Hansen & Larson, 2005) and a modified measure assessing task and outcome interdependence (Van der Vegt, Emans, & Van de Vliert, 1998 Vliert, 2001). Hierarchical multiple regression determined that basketball players reported higher rates of teamwork and social skills, adult networks and social capital, and negative experiences. Furthermore, outcome interdependence was a predictor of identity exploration, initiative, emotional regulation, positive relationships, teamwork and social skills, and adult networks and social capital experiences independent of sport type. Although different sports may provide different learning environments, the developmental experiences youth garner may be more strongly influenced by how the people involved interact (outcome interdependence) than by the type of sport.